PENGEMBANGAN E-MODUL MENGGUNAKAN HEYZINE PADA MATA PELAJARAN INFORMATIKA ELEMEN ANALISIS DATA FASE F KELAS XI SMA NEGERI 13 SAMARINDA - Malika Ramadhani, Suci; Rosita, Dewi; Prayogo, M. Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the limited availability of Informatics teaching materials aligned with the Phase F Kurikulum Merdeka at SMA Negeri 13 Samarinda, particularly in the Data Analysis element. The research aims to develop an interactive and structured digital e-module based on the Heyzine Flipbook. Using the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate), the e-module integrates multimedia features such as videos, enrichment content, quizzes, and case studies. The trial involved 36 students of class XI-3. The results show that the e-module is highly feasible, with material expert scores of 71 and media expert scores of 56.67 (both categorized as very feasible), while student trials scored 47 (feasible). The overall average score of 58.22 indicates that the e-module is very feasible and effective as a practical and relevant independent learning medium to enhance Informatics learning in Data Analysis.